Atención primaria en salud (aps). ¿De regreso al pasado? (2012)
ABSTRACT: Primary health care is analyzed as the alternative through which health systems will recover the role they had during the late twentieth century: working with other sectors to implement health promotion actions to improve the users’ quality of life and equity. A renewal is presented in recognition of the efforts during the final century to establish primary care policies and programs as the core of the health systems, emphasizing the reorientation of health services. This paper discusses the principles and methods established by the new proposal for primary health care. This renewal proposal raises expectations regarding its return to the past, not only as a strategy but also because it raises hopes at a time of global crisis whose impact on health services is evident. The first question posed here is: Is there really a renewal? The discussion focuses on the following topics: phc and the deterioration of health indicators in many areas in the world, social inequalities and health inequities, the weaknesses in the declarations of Alma Ata understood as “medicine for the poor,” the renewal of phc as opposed to the critical health status in countries and the opposing progress of the neoliberal globalization, phc and the political conceptions of the Right, phc and the reform to the reform of the health systems; coordination of phc with health promotion and public health, the changes in the contexts and the new economic crisis in this global event. The paper concludes with a call to revitalize the processes of the health systems from a political standpoint, and to rethink the sanitary reforms of the health systems basing the reasoning on primary health care, which is the focus of their transformation.